**Question**

`The sum of the present ages of a son and his father is 60 years. Six years ago, father's age was five times the age of the son. After 6 years, what will be son's age?`

`The sum of the present ages of a son and his father is 60 years. Six years ago, father's age was five times the age of the son. After 6 years, what will be son's age?`

A. 22 years

B. 23 years

C. 20 years

D. 21 years

**Answer: C. 20 years**

**Solution:**

Let the present age of the son = x

Then, present age of the father = ( 60 − x )

**Six years ago father’s age was 5 times the age of the son **

⇒ ( 60 − x ) − 6 = 5 ( x − 6 )

⇒ 84 = 6x

⇒ x = 84 / 6 = 14

**Son’s age after 6 years **= x + 6

= 14 + 6

= 20

**Hence, The Son’s age after 6 years is 20 years.**